Deteksi Wajah Berbasis Facial Landmark Menggunakan OpenCV Dan Dlib - RR Puji Hajar Sejati; Rodhiyah Mardhiyyah (Universitas Asahan, 2021)
Computer science and information technology have advanced in a variety of sectors that were previously unachievable due to constraints such as hardware. Computer vision can be used to recognize an object using computer science. Objects can be recognized by taking or recording photos or videos and then processing them using specific tools and methodologies. The goal of the facial landmark-based face detection research using OpenCV and Dlib is to perform face detection in people so that it can be used for a variety of purposes in the future. The strategy employed in this study was the usage of facial landmarks using OpenCV and Dlib to improve face detection accuracy. Face detection has been effectively carried out based on facial landmark points, according to the findings of testing the entire system. Face landmark-based face detection is more accurate using the OpenCV Dlib, which can be seen during processing in the OpenCV Dlib, which can precision photos based on facial movements.